Caveolin-1 is required for the upregulation of fatty acid synthase (FASN), a tumor promoter, during prostate cancer progression - Di Vizio, Dolores; Sotgia, Federica; Williams, Terence M.; Hassan, Ghada S.; Capozza, Franco; Frank, Philippe G.; Pestell, Richard G.; Loda, Massimo; Freeman, Michael R.; Lisanti, Michael P. (Cancer biology & therapy, 2007)
Prostate cancer is the second leading cause of cancer-related deaths in men. Fatty acid synthase (FASN) is normally upregulated during human prostate cancer onset and metastatic progression and its expression positively correlates with the development of advanced metastatic disease. However, it remains unknown what molecular factor(s) control FASN expression. It has been hypothesized that FASN functions as a tumor promoter during prostate cancer progression in humans. Consistently, an established mouse of model of prostate cancer, termed TRAMP mice, also shows the progressive upregulation of FASN levels during prostate cancer development. Here, we examine the role of caveolin-1 (Cav-1) in regulating FASN expression during prostate cancer progression. For this purpose, we crossed Cav-1 (-/-) null mice with TRAMP mice to generate TRAMP/Cav-1 (+/+) and TRAMP/Cav-1 (-/-) mice. Then, we assessed the expression of FASN in Cav-1 (+/+) and Cav-1 (-/-) prostate tumors by immunohistochemistry and Western blot analysis. Interestingly, our results indicate that FASN fails to be upregulated in Cav-1 (-/-) tumors. Importantly, the tumors examined were the same morphological grade, but Cav-1 (-/-) tumors were dramatically smaller and did not metastasize efficiently. We conclude that Cav-1 expression is normally required for the upregulation of FASN during prostate cancer progression. These results also mechanistically explain why TRAMP/Cav-1 (-/-) mice are dramatically resistant to the development of prostate tumors and lung metastases, as they lack the expression of the FASN tumor promoter. Thus, TRAMP/Cav-1 (-/-) mice will provide a novel model system to elucidate the role of FASN in prostate tumor progression. In addition, our results provide the first molecular genetic evidence that Cav-1 functions upstream of FASN during prostate cancer progression.